OHP-010 Management of parenteral nutrition in the Intensive Care Unit of a third level hospital. (24th February 2014) - Briones, E; Barbadillo, S; Pedrosa, MA; Oca, B; López, A; Martínez, R; Benito, V; Alonso, S; González, V; Güemes, M
Abstract : Background: Critically ill patients are characterised by hypercatabolism, representing a higher risk of malnourishment. In these patients, both nutrient deficits and overfeeding are harmful. Parenteral nutrition (PN) is an alternative approach when it is not possible to use other routes. Purpose: To analyse the management of PN by prescribers in the intensive care unit (ICU) of our hospital, and their observance of the guidelines of scientific societies ESPEN and SENPE. Materials and methods: A retrospective, observational study of ICU patients with PN support from June to August 2013. Data were collected from the Kabisoft 2012 PN software: age, diagnosis, duration of PN support, calories and protein supplied, types of lipid emulsion provided, addition of glutamine, and management of volume and hyperglycaemia. Results: 21 patients were studied, median age was 70 (49–83). Reason for ICU admission was postoperative (9), septic shock (6), hypovolemic shock (2), traumatism (2), acute pancreatitis (1) and acute renal failure (1). Median number of days with PN was 8 (1–46). Calories provided were fewer than 25 Kcal/Kg in 85.7% of patients and 25–30 Kcal/Kg in 14.3%. Regarding protein input, 76.2% patients received less than 1.3 g/Kg and 23.8% between 1.3–1.5 g/Kg. Forty patients (66.7%) received mixed MCT/LCT lipid emulsion, 5 (23.8%) fish-oil enriched emulsion, and 2 (9.5%) received both lipid emulsions. 38.1% PN bags were supplemented with glutamine (less than 0.2 mg/Kg). Prescribers tried to reduce the volume in 42.8% PN, and 28.6% added insulin to the PN. Conclusions: Clinical practice patterns related to PN management in ICU did not follow ESPEN and SENPE guidelines in most of the cases. According to Jeejeebhoy K. N. 2012, an adequate protein delivery is required to obtain an optimal benefit, independently of whether energy goals are reached. In our study, a high percentage of patients were underfed, receiving an amount of both calories and protein lower than recommended. No conflict of interest.